Multiple Representation-Based Blended Learning Model for Chemistry Learning in High School - Mulyani, Sri; Susanti VH, Elfi; Ariani, Sri Retno Dwi; Utomo, Suryadi Budi; Kharolinasari, Rachma; Panie, Maria Yuliana (PAEDAGOGIA, 2022)
Online distance learning during the COVID-19 outbreak presents new challenges and opportunities for teachers and students. The Blended Learning method is reported to be one of the promising alternatives. However, no specific study revealed the proper blended learning model for chemistry learning that require chemistry representation and can improve critical thinking and problem solving skills at high school level. Qualitative research using phenomenological methods was used in this study. The data collection technique used is using questionnaires, interviews, and documentation. A total of 22 respondents from master students of chemistry education, lecturers and teachers of chemistry education participated in this study. The blended learning model analyzed in this study are Rotational blended learning models (station class, Lab/Whole Group class, flipped class, and Individual), Flex, Self-Blend, and Enriched-Virtual classes. The study results indicate that the blended learning model that the respondents chose the most suitable for multiple representation-based chemistry learning was the Flipped Class model (50%), while the one that was not selected was the Individual Rotation model.